Conservative in theology, liberal in spirit modernism and the American Presbyterian mission in Thailand, 1891-1941 - Dahlfred, Karl (Pickwick Publications, 2024)
"In the early twentieth century, theological modernism was gaining ground in the Presbyterian Church in the U.S.A. Conservatives claimed that there were modernists on the mission field but that the Board of Foreign Missions was doing nothing about it. In Thailand, the executive secretary of the American Presbyterian mission did not want to address the issue, claiming that 'almost all of our Mission... are conservative in their theology, and liberal in their spirit.' But was it true? In this book, Karl Dahlfred explores letters, reports, and other primary sources to reveal instances and indicators of modernism among Presbyterian missionaries in Thailand. Officially committed to making disciples of Jesus Christ, American Presbyterian missionaries were increasingly divided over what that meant, and how to carry out their task. Were schools or evangelism the best mode of Christian influence? Did the gospel need adjustment for the modern world? The mission formally maintained a conservative consensus, yet modernism was present. And fundamentalist-minded missionaries were not happy about it. Scholars, missionaries, Thai Christians, and anyone interested in mission history or the long-term trajectory of Protestant work in Thailand will enjoy this exploration of an overlooked chapter in the history of Christianity in Thailand."--Back cover
Keywords: Presbyterian Church in the U.S.A. / Missions; Missions, American / Thailand / History / 19th century; Missions, American / Thailand / History / 20th century; Modernism (Christian theology) / Presbyterians; Protestant churches / Thailand; Missions / Thailand; Thailand / Church history; Missions américaines / Thaïlande / Histoire / 19e siècle; Missions américaines / Thaïlande / Histoire / 20e siècle; Modernisme (Théologie chrétienne) / Presbytériens; Églises protestantes / Thaïlande